A deadly affair at Bobtail Ridge : a Samuel Craddock mystery - Shames, Terry (Shames, Terry. Samuel Craddock mystery., 2015)
"In a small town in East Central Texas, Samuel Craddock has learned to accept that his friend Jenny Sandstone's personal life is strictly secret. But when Jenny's dying mother tells Craddock that Jenny is in danger, he is confronted with a dilemma. He wants to respect Jenny's privacy, but he is haunted by the urgency in the dying woman's voice. Forced to confront the past, Jenny plunges into a downward spiral of rage and despair. Craddock knows that only by solving the mystery of secrets buried in her past, can he hope to save Jenny both from herself and from whoever is out to harm her"--